STUDENTS' TEST CONTROL: ADVANTAGES AND ISADVANTAGES - I.A. Kolesnik (Ukrainian Medical Stomatological Academy, 2017)
The transition of the educational activities of higher educational institutions to credit-transfer system provides for the continuous improvement of the quality of education to ensure a high level of graduates' training that presupposes the development, implementation of the new or enhancement of existing methods of teaching material presentation, upgrading of methods of instruction and improving of the quality control of the students' learning. One of the stimuli of study is a systematic control, carried out by the educator. The role of the teacher is to intensify students' educational and cognitive activity, monitor the process of knowledge acquisition and its assessment. In the contemporary system of education testing takes a special place during the assessment of students' knowledge and is widely used for both checking the initial level of knowledge acquisition, and current or final control. Therefore, our study was aimed at the analysis of the advantages and disadvantages of test control in the system of medical education, which was carried out at the Department of Children's Dental Surgery with Propaedeutics during the study of the "Propaedeutics of Dental Surgery" module. The significant benefits of testing for teachers could be the possibility of simultaneous assessment of a large group of students for a relatively short time, the widespread coverage of the material as compared to the recitation, contributing to assessment of knowledge of each student not for one specific question, but the knowledge of the whole topic. Testing, carried out at each lesson leads students to the systematic study of the material, ensures the objectivity of the assessment of knowledge and lack of psycho-emotional tension that can arise during recitation. Inadequate quality of tests, cheating and giving the correct answer at random, standard thinking without considering the development of student's personality can be assigned to testing limitations. Oral communication between a teacher and students can be beneficial in learning how to use special medical terminology, express the thoughts clearly, build a sentence properly and logically that is not provided by the testing. Situational tasks solution with a variety of clinical cases, as well as the analysis of case patients, allowing the students to acquire not only theoretical knowledge, but also some practical skills is of great importance in the learning process. This leads to reflections, contributing to learning not only how to understand and acquire information, but also analyze it and think clinically that is an important criterion for the future physician. So, testing is a convenient, reliable and objective method of evaluation. Despite the large number of advantages of the test control, it is necessary to combine various forms of control: test control, recitation, situational tasks solution, analysis of clinical patients, etc.